Evaluating a Fingerprint-Based Employee Attendance System Using UAT and the PIECES Framework - Tria Angelika Br Simatupang; Yohana Rodiagogo Manik; Fince Tinus Waruwu (STMIK Methodist Binjai, 2026)
The development of information technology has encouraged companies to implement fingerprint-based attendance systems to improve the effectiveness and accuracy of employee attendance recording. However, in its implementation, several problems are still found, such as system errors, delays in fingerprint reading, and technical disturbances that can affect user convenience. This study aims to evalUATe the fingerprint-based attendance information system at PT GIRVI MASS using the User Acceptance Testing (UAT) method and the PIECES Framework. The UAT method was used to measure the level of user acceptance toward the system, while the PIECES Framework was applied to analyze system quality based on the aspects of Performance, Information, Efficiency, and Service. This research used a quantitative method by distributing questionnaires with a Likert scale to 30 respondents who were employees of PT GIRVI MASS. The collected data were analyzed using the weighted mean method and UAT percentage calculations. The results showed that the system obtained a UAT percentage score of 82.6%, which falls into the “Very Good” category. The PIECES Framework analysis also indicated that the system was able to improve the attendance process to become more effective, efficient, and user-friendly. Nevertheless, several technical issues were still identified, especially related to system stability and error handling. Therefore, the company is advised to conduct regular maintenance and system development to further improve system quality in the future